TAFSIR ISYARI DALAM CORAK PENAFSIRAN IBNU 'ARABI - Zuherni AB (South East Asia Regional Intellectual Forum of Qoran Hadith (SEARFIQH), 2016)
The teachings of Sufism is a heresy that led to the decline of Muslims. But the reality proves that al-Quran as a guide to human life not only speaks to the human intellect alone, but also to his heart. If the Koran is only understood through reason, there will be a spiritual drought in the Shari'ah. If the Koran is only understood through a careful approach course there will be inbalance in shari'ah. The mystics with a popular interpretation to the term interpretation isyari try to capture the messages of God in Sufi words (isyari). One among many is traveller Sufi Ibn 'Arabi. Ibn 'Arabi tried to understand the word of God as a whole and integral. In addition, he also includes figures who gave birth to the Sufi teachings are considered controversial in the history of intellectual Islam thatis wahdat al-wujud (Existence in Unity). With the known mode of interpretation of Ibn 'Arabi, it can also be shown that the method used in Ibn' Arabi in interpreting the Koran and how the validity of the teachings of Ibn 'Arabi as a result of the interpretation of the Koran.